An analysis of probability of area techniques for missing persons in Yosemite National Park - Doherty, Paul J.; Guo, Quinghua; Doke, Jared; Ferguson, Don (Applied geography (Sevenoaks), 2014)
Study of wilderness search and rescue (WiSAR) incidents suggests a dependency on demographics as well as physical geography in relation to decisions made before/after becoming lost and subsequent locations in which subjects are found. Thus an understanding of the complex relationship between demographics and physical geography could enhance the responders' ability to locate the subject in a timely manner. Various global datasets have been organized to provide general distance and feature based geostatistical methods for describing this relationship. However, there is some question as to the applicability of these generalized datasets to local incidents that are dominated by a specific physical geography. This study consists of two primary objectives related to the allocation of geographic probability intended to manage the overall size of the search area. The first objective considers the applicability of a global dataset of lost person incidents to a localized environment with limited geographic diversity. This is followed by a comparison between a commonly used Euclidean distance statistic and an alternative travel-cost model that accounts for the influence of anthropogenic and landscape features on subject mobility and travel time. In both instances, lost person incident data from years 2000 to 2010 for Yosemite National Park is used and compared to a large pool of internationally compiled cases consisting of similar subject profiles. •Differences observed in SAR incident datasets for similar terrain and environments.•Cost-distance model provides accurate assessment of cross country travel time.•Trends observed in travel time for lost persons in a wilderness environment.